Diffusion-weighted MRI in herpes simplex encephalitis: a report of three cases. - Küker, W; Nägele, T; Schmidt, F; Heckl, S; Herrlinger, U (2004)
Herpes simplex virus encephalitis (HSVE) is the most frequent fatal viral infection of the brain. Because antiviral treatment may improve the prognosis significantly, early diagnosis is mandatory. Imaging diagnosis rests on conventional MRI for the visualization of lesions in the limbic system, the hallmark of HSVE. Diffusion-weighted MRI (DW-MRI) has not been used for the evaluation of HSVE. We report on the DW-MRI findings in three patients with HSVE, who had cortical diffusion abnormalities in affected brain parenchyma, partially as the initial or most sensitive sign of encephalitis. Sequential imaging showed that the diffusion abnormality started to return to normal after 2 weeks in the presence of persistent contrast uptake. Thus, DW-MRI may be a valuable tool for early detection and diagnosis of HSVE whereas contrast-enhanced images are indispensable after the first week.